SAINTIS DAN PEMBANGUNAN MASYARAKAT: APA SUMBANGAN AL-ZAHRĀWĪ BERASASKAN BUKUNYA AL-TASRĪF LI MAN ‘AJIZA ‘AN AL-TA’LĪF ? - Sidik@Mat Sidek, Roziah (Journal of Al-Tamaddun, 2009)
This article explains the role of scientist towards the development of the society. It focuses on the contribution of al-Zahrawi as a scientist during 10th century who flourished in the west of Islamic region towards the development of the society. This article is written based on library research by thoroughly looking and filtering information from primary as well as secondary sources. The result shows that al-Zahrawi gives many contributions to the development of society. Among his contributions are providing information on the knowledge of medicine which was not only can be achieved but also can be refered by the society through the production of his outstanding works al-Tasrif li Man 'Ajiza 'an al-Ta'līf, existing of high quality of surgeon, providing space for good service in medical supervision, liven the activity of translation and developing field of medicine in Europe especially related to surgery. Therefore, his contribution is not only focused on Andalusian but also to European.